Stiftung Anne-Marie und Victor Loeb. - Jolles, Paul R.; Szeemann, Harald; Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1978)
Agam, Yaacov ; Albers, Josef ; Alviani, Getulio ; Archipenko, Alexander ; Ben ; Beuys, Joseph ; Bill, Max ; Bogart, Bram ; Boltanski, Christian ; Bury, Pol ; Buthe, Michael ; Calderara, Antonio ; de Camargo, Sergio ; Christo ; Cruz-Diez, Carlos ; Dali, Salvador ; Darboven, Hanne ; Dewasne, Jean ; Diller, Burgoyne ; Duchamp, Marcel ; Ernst, Max ; Errò ; Fontana, Lucio ; Francis, Sam ; Gac, Jean Le ; Gerstner, Karl ; Glarner, Fritz ; Gorin, Jean ; Graeser, Camille ; Graubner, Gotthard ; Harloff, Guy ; Herbin, Auguste ; Honegger, Gottfried ; Itten, Johannes ; Jensen, Alfred ; Kandinsky, Wassily ; Kassak, Lajos ; King, Phillip ; Klee, Paul ; Klein, Yves ; Kunz, Emma ; Kupka, Frantisek ; Leger, Fernand ; LeWitt, Sol ; Lissitzky, El ; Lohse, Richard Paul ; Luginbühl, Bernhard ; Mack, Heinz ; Magritte, René ; Malevich, Kasimir ; Mangold, Robert ; Manzoni, Piero ; Marden, Brice ; Martin, Agnes ; Martin, Etienne ; Megert, Christian ; Moholy-Nagy, Laszlo ; Moore, Henry ; Moses, Ed ; Müller, Bruno ; Nebel, Otto ; Nevelson, Louise ; Oppenheim, Meret ; Paolini, Giulio ; Pasmore, Victor ; Riley, Bridget ; Rothko, Mark ; Sandback, Frederick Lane ; Schoonhoven, Jan ; Sonnier, Keith ; Soto, Jesus Rafael ; Soutter, Louis ; Spoerri, Daniel ; Stella, Frank ; Sugerman, George ; Taeuber-Arp, Sophie ; Tanguy, Yves ; Thek, Paul ; Thomkins, André ; Tinguely, Jean ; Tschumi, Otto ; Tuttle, Richard ; Uecker, Günther ; Vantongerloo, Georges ; Vasarely, Victor ; Verheyen, Jef ; Visser, Carel Nicolas ; Vordemberge-Gildewart, Friedrich ; Weber, Willy ; Werro, Roland
geboortedata per kunstenaar
Duits
Stiftung Anne-Marie und Victor Loeb, Kunsthalle Bern, 4. März bis 9. April 1978
boek